The Transformation of Islamic Boarding Schools in the Digital Era: A Case Study of Three Islamic Educational Institutions in Indonesia - Juhri; Andi Baso Muammar Assaad; Marjan Drakel; Subhan Abdullah (CV. Creative Tugu Pena, 2026)
This study investigates how Islamic boarding schools respond to digital transformation while maintaining religious traditions and core Islamic values. The research focuses on identifying leadership strategies, management practices, and learning innovations implemented to harmonize technological advancement with pesantren traditions. Employing a qualitative intrinsic case study design, the study was conducted in three Islamic boarding schools in Indonesia: Al-Muayyad (Solo), Nurul Jadid (Probolinggo), and IMMIM Putra (Makassar). Data were gathered through in-depth interviews, participatory observations, and document analysis, and subsequently examined using thematic analysis based on the Braun and Clarke framework. The findings reveal that digital transformation in pesantren extends beyond the adoption of digital tools and involves a fundamental shift in leadership orientation and educational management. Kyai play a central role as value-based transformational leaders who guide digital innovation while safeguarding spiritual principles and ethical learning traditions. The institutions developed hybrid learning models that integrate classical halaqah and tahfidz practices with digital platforms such as e-learning systems and online da’wah media. However, challenges remain, particularly related to uneven technological infrastructure and limited digital literacy among educators. This study proposes a conceptual model of value-based leadership in pesantren digital transformation and offers strategic insights for Islamic education policy development that remains adaptive to technological change while rooted in traditional values.